Cancer mortality among Brazilian dentists. Issue 11 (27th August 2014) - Koifman, Sergio; Malhão, Thainá Alves; Pinto de Oliveira, Gisele; de Magalhães Câmara, Volney; Koifman, Rosalina Jorge; Meyer, Armando
<x xml:space="preserve">Abstract</x> Background Previous studies have variably shown excess risks of elected cancers among dentists. Methods National Brazilian mortality data were used to obtain mortality patterns among dentists between 1996 and 2004. Cancer mortality odds ratios (MORs) and cancer proportional mortality ratios for all cancer sites were calculated, using the general population and physicians and lawyers as comparison groups. Results Female dentists from both age strata showed higher risks for breast, colon‐rectum, lung, brain, and non‐Hodgkin lymphoma. Compared to physicians and lawyers, higher MOR estimates were observed for brain cancer among female dentists 20–49 yr. Among male dentists, higher cancer mortality was found for colon‐rectum, pancreas, lung, melanoma, and non‐Hodgkin lymphoma. Higher risk estimates for liver, prostate, bladder, brain, multiple myeloma and leukemia were observed among 50–79 yr old male dentists. Discussion If confirmed, these results indicate the need for limiting occupational exposures among dentists in addition to establishing screening programs to achieve early detection of selected malignant tumors. Am. J. Ind. Med. 57:1255–1264, 2014. © 2014 Wiley Periodicals, Inc.